2018
DOI: 10.3892/ol.2018.8139
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl disulfide effect on the invasion and migration ability of HL-60 cells with a high expression of DJ-1 in the nucleus through the suppression of the Src signaling pathway

Abstract: The present study examined the effect of diallyl disulfide (DADS) on the invasion and migration ability of HL-60 cells with a high expression of parkinsonism associated deglycase (DJ-1) in the nucleus (HHDN), and its molecular mechanism. A western blot assay was used to measure the effects of DADS and an Src inhibitor on the expression of DJ-1 and the Src signal pathway in HHDN. The effects of DADS and Src inhibitors on the invasion and migration ability of HHDN was detected using Transwell migration and invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The anticancer potency of DADS has been explored in vitro and in vivo studies. 4,20,23 The MTT results showed that DADS apparently inhibited growth and survival of U2OS and MG-63 cells in a concentrationas well as time-dependent manner. Cell colony formation and transwell assays further revealed that DADS treatment showed antiproliferation and anti-invasion properties in OS cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anticancer potency of DADS has been explored in vitro and in vivo studies. 4,20,23 The MTT results showed that DADS apparently inhibited growth and survival of U2OS and MG-63 cells in a concentrationas well as time-dependent manner. Cell colony formation and transwell assays further revealed that DADS treatment showed antiproliferation and anti-invasion properties in OS cells.…”
Section: Discussionmentioning
confidence: 99%
“…This emphasizes the need for the development for safer, natural, and nontoxic compounds as chemotherapeutic agents. The anticancer potency of DADS has been explored in vitro and in vivo studies . The MTT results showed that DADS apparently inhibited growth and survival of U2OS and MG‐63 cells in a concentration‐ as well as time‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Diallyl disulfide (DADS) has anti-cancer potential, and treatment with DADS induces apoptosis and inhibits the metastatic potential of leukemia cells by suppressing the expression of oncoproteins, including PARK7 [128]. DADS inhibits the activation of Src and focal adhesion kinase (FAK) by reducing the expression of PARK7 [129].…”
Section: Therapies Targeting Park7mentioning
confidence: 99%
“…The synthetic antifungal agent Ciclopirox olamine has been reported to downregulate DJ-1 expression leading to mitochondrial dysfunction and ROS accumulation, thereby inhibiting colorectal cancer growth (Zhou et al, 2019). Furthermore, diallyl disulfide reduced DJ-1 expression that suppresses the Src pathway, leading to induction of apoptosis and inhibition of metastasis potential of leukemia cells (Liu et al, 2018). In addition, the DJ-1 suppression efficacy of paclitaxel leads to the inhibition of breast cancer metastasis (Ismail et al, 2018) and the transformation of NIH3T3 cells (MacKeigan et al, 2003) has been evaluated.…”
Section: Cancermentioning
confidence: 99%